2010
DOI: 10.1080/11745398.2010.9686839
|View full text |Cite
|
Sign up to set email alerts
|

‘It's a Form of Freedom’: The experiences of people with disabilities within equestrian sport

Abstract: This paper explores the embodied, gendered experiences of disabled horse-riders. Drawing on data from five in-depth interviews with para-dressage riders, the ways in which their involvement in elite disability sport impacts upon their sense of identity and confidence are explored, as well as the considerable health and social benefits that this involvement brings. Social models of disability are employed and the shortcomings of such models, when applied to disability sport, are highlighted. The data presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Taking into account that resources for this group are limited [ 31 ], when the financial costs of sporting activities increase, a barrier to participation is formed. In this sense, being a woman can also be an added barrier, as it can be more difficult to obtain sporting sponsors [ 68 ]. It is clear that for women with physical disabilities to benefit from sport, an approach that involves a wider range of programs is required.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that resources for this group are limited [ 31 ], when the financial costs of sporting activities increase, a barrier to participation is formed. In this sense, being a woman can also be an added barrier, as it can be more difficult to obtain sporting sponsors [ 68 ]. It is clear that for women with physical disabilities to benefit from sport, an approach that involves a wider range of programs is required.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research involving para-athletes reported the pursuit of sportsrelated health benefits where the adaptive equipment affords such freedom (eg, horse riding in equestrian). 27 In contrast to this, research in elite sport has reported suppression of HSBs where disability has been emphasized with the use of assistive/ mobility devices. 28 Wider relationships and forming trust positively or negatively influenced HSBs.…”
Section: Discussionmentioning
confidence: 99%
“…A positive significance linking HSBs with an athlete’s identity is feeling freedom with sports participation. Previous research involving para-athletes reported the pursuit of sports-related health benefits where the adaptive equipment affords such freedom (eg, horse riding in equestrian) 27 . In contrast to this, research in elite sport has reported suppression of HSBs where disability has been emphasized with the use of assistive/mobility devices 28 …”
Section: Discussionmentioning
confidence: 99%
“…Параспорт делает инвалидность «видимой» не только в спорте, но и для общества в целом [Purdue, Howe, 2012b], а также является площадкой для расширения прав и возможностей людей с инвалидностью [Purdue, Howe, 2012a;Braye, 2016]. К позитивным последствиям вовлеченности в профессиональный спорт для людей с инвалидностью относят: расширение жизненных перспектив спортсменов; возможность преодолеть негативную идентификацию, повышение уверенности спортсменов с инвалидностью в собственных возможностях; медицинские (улучшение здоровья и самочувствия) и социальные выгоды (улучшение материального положения, расширение круга общения, путешествия) [Ashton-Shaeffer et al, 2001;Dashper, 2010]. Чтобы избежать излишней идеализации спорта как способа расширения социальных и физических возможностей людей с инвалидностью, стоит также отметить, что преодоление барьеров и сложностей является неотъемлемой частью большого спорта [Purdue, Howe, 2012a].…”
unclassified